2013
DOI: 10.1007/s11250-013-0491-3
|View full text |Cite
|
Sign up to set email alerts
|

Methane emission of Santa Inês sheep fed cottonseed by-products containing different levels of gossypol

Abstract: The aim of this study was to evaluate the methane (CH4) emission of Santa Inês sheep fed cottonseed by-products, verifying if the gossypol content of these feedstuffs affects CH4 emission. Twelve late-lactating Santa Inês sheep (44.8 ± 7.5 kg body weight (BW)) were allocated in metabolic cages for an experimental period of 19 days, 14 days for adaptation and 5 days for measuring CH4 emission and dry matter intake (DMI). The animals were divided into four treatments, established in accordance with the cottonsee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 14 publications
1
2
0
2
Order By: Relevance
“…In our study, we found that gossypol supplementation had no impact on DMI. This result is similar to previous reports showing that different feed levels of gossypol contained in cottonseed had no impact on DMI in sheep [28]. Similarly, no difference in feed consumption was found when comparing high and low levels of gossypol feed in lambs [29].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, we found that gossypol supplementation had no impact on DMI. This result is similar to previous reports showing that different feed levels of gossypol contained in cottonseed had no impact on DMI in sheep [28]. Similarly, no difference in feed consumption was found when comparing high and low levels of gossypol feed in lambs [29].…”
Section: Discussionsupporting
confidence: 91%
“…The main controlling factor of plasma urea concentrations is the formation of ammonia in the rumen, and the concentration of plasma urea appears to reflect changes in rumen ammonia production. Thus, the concentration of urea in the plasma is influenced by the extent to which the absorbed amino acids are oxidized and by the absorption of ammonia from the rumen, substantially reflecting the extent of nitrogen balance in the animal, considering both the requirements of ruminal microorganisms and of the host animal ( Lima, 2013 ). Ionophores, such as monensin and narasin, are potential feed additives to decrease rumen ammonia, especially to inhibit deamination ( Bergen et al, 1984 ), which could decrease plasma urea concentration; however, this was not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Enteric methane emissions were measured by using sulphur hexafluoride (SF6) tracer technique described by Johnson et al (1994), with adaptations by Primavesi et al (2004), Moreira et al (2013) and Lima et al (2014) regarding permeation tubes and yokes.…”
Section: Estimation Of Ch4 Productionsmentioning
confidence: 99%